Islāmic finance and poverty reduction in African countries: an empirical analysis - Adamu Ahmed, Wudil; Saad, Norma; Omercic, Jasmin; Lacheheb, Zakaria; Rislanudeen, Muhammad (IIUM Press, 2025)
This paper examined the effect of Islamic finance on poverty reduction in 53 African countries over the period 2013 to 2022. Islamic finance, based on Islamic principles and values, emphasizes ethical conduct, social responsibility, and promotion of social welfare. Poverty remains a pressing issue in many African countries, and traditional financial systems have for long struggled to effectively address this challenge. Islamic finance offers unique features and mechanisms that can contribute to poverty reduction efforts. This study employs a panel System Generalized Method of Moments (SGMM) estimation technique and explores the empirical evidence on the relationship between Islamic finance development and poverty reduction, while controlling for other variables such as foreign aid, government budgets, and government effectiveness. The findings indicate that Islamic finance development, foreign aid, and government budgets have significant positive effects on poverty reduction, while government effectiveness has a negative effect. Thus, the findings highlight the potential of Islamic finance in poverty reduction in African countries and provide valuable insights for policymakers, practitioners, and researchers in harnessing the benefits of Islamic finance for inclusive and sustainable development